Analisis Sistem Persediaan Pada CV Tanaka Service - Ita Mustika; Defri Defri; Tiara Novia Piska (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
This study aims to determine whether the implementation of inventory systems and procedures applied to CV. Tanaka Service is in accordance with the objectives of internal control. To obtain the necessary data, the authors use data collection tools in the form of interviews and decisions. The data analysis method used is descriptive qualitative data From the results of the research, it can be concluded that the existing system in CV. Tanakan Service has not been carried out effectively. This can be seen from the company does not have its own internal control system and does not have adequate storage space, there is a lot of damage and expired goods in the warehouse, so there is a stock opname policy in maintaining the availability of merchandise inventory but is supported by the use of stock cards as a basis for inventory control. merchandise. And the implementation of information and communication as well as monitoring is dominated only by the director.